Cardiovascular System Under Simulated Weightlessness: Head-Down Bed Rest vs. Dry Immersion - Amirova, Liubov; Navasiolava, Nastassia; Rukavishvikov, Ilya; Gauquelin-Koch, Guillemette; Gharib, Claude; Kozlovskaya, Inessa; Custaud, Marc-Antoine; Tomilovskaya, Elena (Frontiers in Physiology, 2020)
Background The most applicable human models of weightlessness are −6° head-down bed rest (HDBR) and head-out dry immersion (DI). A detailed experimental comparison of cardiovascular responses in both models has not yet been carried out, in spite of numerous studies having been performed in each of the models separately. Objectives We compared changes in central hemodynamics, autonomic regulation, plasma volume, and water balance induced by −6° HDBR and DI. Methods Eleven subjects participated in a 21-day HDBR and 12 subjects in a 3-day DI. During exposure, measurements of the water balance, blood pressure, and heart rate were performed daily. Plasma volume evolution was assessed by the Dill–Costill method. In order to assess orthostatic tolerance time (OTT), central hemodynamic responses to orthostatic stimuli, and autonomous regulation, the 80° lower body negative pressure–tilt test was conducted before and right after both exposures. Results For most of the studied parameters, the changes were co-directional, although they differed in their extent. The changes in systolic blood pressure and total peripheral resistance after HDBR were more pronounced than those after DI. The OTT was decreased in both groups: to 14.2 ± 3.1 min (vs. 27.9 ± 2.5 min before exposure) in the group of 21-day HDBR and to 8.7 ± 2.1 min (vs. 27.7 ± 1.2 min before exposure) in the group of 3-day DI. Conclusions In general, cardiovascular changes during the 21-day HDBR and 3-day DI were co-directional. In some cases, changes in the parameters after 3-day DI exceeded changes after the 21-day HDBR, while in other cases the opposite was true. Significantly stronger effects of DI on cardiovascular function may be due to hypovolemia and support unloading (supportlessness).